(untitled) - Wallwork, Adrian (London, 2011)
This guide is based on a study of referees' reports and letters from journal editors on reasons why papers written by non-native researchers are rejected due to problems with English usage. It draws on English-related errors from around 5000 papers written by non-native authors, 500 abstracts by PhD students, and over 1000 hours of teaching researchers how to write and present research papers.
Keywords: Linguistics.,English language,Tiếng Anh,Ngôn ngữ học; Technical English.,Kỹ thuật tiếng Anh